Viejo House - Mathias Klotz (Oz, 2003)
The Viejo Residence is a single-family house located in a Santigao neighborhood dating from the 1950s. The original traditional-style residence was demolished. In its place we designed this new house that takes advantage of the original garden with its fantastic fifty-year-old trees.